PERNIKAHAN USIA DINI DI INDONESIA PANDANGAN HUKUM ISLAM DAN HUKUM POSITIF - Fildza Rasiqah (Yayasan Nurul Yaqin Annaba, 2025)
Early marriage is a marriage that takes place when the bride is under 16 years old and the groom is under 19 years old. Internal factors come from within the individual, such as their own desires, while external factors include the parents' economic situation, education, and the parents' wishes. Many teenagers are trapped in early marriages, especially those from disadvantaged families, who choose to marry at a young age to alleviate their family's economic burden. There are numerous risks associated with early marriage, both physical and psychological. Research findings indicate that various factors influence early marriage. The primary cause is economic factors, with supporting factors including peer influence, the desires of the individual, family, and pregnancy outside of marriage.